EMPLOYABILITY SKILLS REQUIRED OF OFFICE TECHNOLOGY AND MANAGEMENT GRADUATES BY MANAGERS OF SMALLSCALE ENTERPRISES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study was conducted to ascertain the employability skills required of office technology andmanagement (OTM) graduates by small scale enterprises in Anambra State. The study adopted adescriptive Survey design. Two research questions guided the study, while two hypotheses weretested at 0.05 level of significance. Population of 980 mangers of small scale enterprise wasused for the study. Proportionate stratified sampling techniques were used to sample 294 smallscale enterprise managers in Anambra State. The questionnaire was validated by experts inbusiness education. The reliability method was used to determine the reliability of the instrumentwas established using Cronbach alpha formula to determine the internal consistency of theinstrument which yielded Correlation coefficient values of 0.93, 0.97, 0.98, and 0.96 for the fourclusters of the questionnaire, with the overall coefficient value of 0.96. Mean was used to answerthe research questions while the null hypothesis were tested at 0.05 level of significance using Ztest. Data collected were analyzed using arithmetic mean and standard deviation to answer theresearch questions. Findings from the study revealed that problem solving skill, and databaseadministration skills, are highly required of OTM graduates by small scale enterprises inAnambra State.
Keywords: Employability Skill, Skills, Office Technology, Office Technology and Management Graduates and Small-Scale Enterprises